Actual Cleaning and Simulated Cleaning Attenuate Psychological and Physiological Effects of Stressful Events. Issue 4 (May 2023) - Lee, Spike W. S.; Millet, Kobe; Grinstein, Amir; Pauwels, Koen H.; Johnston, Phillip R.; Volkov, Alexandra E.; van der Wal, Arianne J.
The human mind harbors various mechanisms for coping with stress, but what role does physical behavior play? Inspired by ethological observations of autogrooming activity across species, we offer a general hypothesis: cleaning attenuates effects of stressful events. Preregistered behavioral and psychophysiological experiments ( N = 3, 066 in United Kingdom, United States, and Canada) found that (a) concrete visual simulation of cleaning behavior alleviated residual anxiety from a stress-inducing physical scene, an effect distinct from touch, and (b) actual cleaning behavior enhanced adaptive cardiovascular reactivity to a highly stressful context of social performance/evaluation, which provides the first physiological evidence for the attenuation of stress-related effects by cleaning. Overall, actual cleaning and simulated cleaning attenuate effects of physical or psychological stressors, even when they have nothing to do with contamination or disease and would not be resolved by cleaning. Daily cleaning behavior may facilitate coping with stressors like physical risks and psychological threats to the self.